Enhancing the performance of heaving wave energy converters using model-free control approach. (November 2015) - Jama, M.A.; Noura, H.; Wahyudie, A.; Assi, A.
Abstract: This paper investigates the application of model free control (MFC) strategy to optimally control the oscillation of single body heaving waves energy converter (WEC). The aim of the proposed controller is to maximize the electrical energy output of the device. The MFC is an off-line fixed structure control approach that combines between simplicity and insensitivity to system uncertainties and/or operational conditions. The proposed controller is based on a classical linear compensator, which is designed and tuned using only the well-known dynamics of the WEC. Therefore, any extra unknown or partially known dynamics are taken care of using the ultra-local model (ULM). Simulation results show that the MFC performance is superior to that of the base linear compensator, in terms of reference tracking capability and robustness towards uncertainties. Also other well-established control strategies are used to further validate the proposed controller. Highlights: A simple and robust control strategy for controlling heaving wave energy converter (WEC) is proposed. The control strategy consists of a lead compensator and an ultra-local model (ULM) component. Simulations proved the effectiveness of the proposed controller by comparing it to other control strategies. The MFC strategy outperformed other control strategies in maximizing the captured power and being immune to uncertainties.